In vitro Activity and Heteroresistance of Omadacycline Against Clinical Staphylococcus aureus Isolates From China Reveal the Impact of Omadacycline Susceptibility by Branched-Chain Amino Acid Transport System II Carrier Protein, Na/Pi Cotransporter Family Protein, and Fibronectin-Binding Protein - Bai, Bing; Lin, Zhiwei; Pu, Zhangya; Xu, Guangjian; Zhang, Fan; Chen, Zhong; Sun, Xiang; Zheng, Jinxin; Li, Peiyu; Deng, Qiwen; Yu, Zhijian (Frontiers in Microbiology, 2019)
Omadacycline (Omad), a new tetracycline (Tet)-class broad-spectrum aminomethylcycline, has been reported to exhibit excellent potency against Gram-positive bacteria, including Staphylococcus aureus and Enterococci. The aim of this study was to evaluate the in vitro activity and heteroresistance characteristics of Omad in clinical S. aureus isolates from China and investigate Omad resistance mechanisms. A sample of 263 non-duplicate clinical S. aureus isolates [127 methicillin-resistant (MRSA) and 136 methicillin-sensitive (MSSA)] were collected retrospectively. Our data indicated that Omad exhibited excellent in vitro activity against both MRSA and MSSA. Omad heteroresistance frequencies were 3.17% (4/126) in MRSA and 12.78% (17/133) in MSSA. No mutations in Tet target sites, (five 16SrRNA copies and 30S ribosomal protein S10) were present in heteroresistance-derived clones, whereas Tet target site mutations contribute to induced Omad resistance in S. aureus in vitro. RNA sequencing (RNA-Seq) revealed that overexpression of branched-chain amino acid transport system II carrier protein and Na/Pi cotransporter family protein contributes to Omad heteroresistance emergence. Whole-genome sequencing demonstrated that the genetic mutation of fibronectin-binding protein (FnBP) could increase the Omad MIC. In conclusion, Omad heteroresistance risk should be considered in clinical isolates with MICs ≥ 0.5 mg/L and Omad susceptbility in S. aureus may be affected by efflux pump proteins (i.e. a branched-chain amino acid transport system II carrier protein and an Na/Pi cotransporter family protein), and FnBP.